PROFIL PERSONALITY WITA WITARSA - HINGIS MOUDINA ENGGAR SUKMA; Tandiyo Rahayu; Rumini (Universitas Negeri Semarang, 2024)
Wita Witarsa ​​is a lecturer in sports and a long-distance athletic trainer in Indonesia. In this research, the researcher will discuss Wita Witarsa's personality, the writing of which focuses on important things in Wita Witarsa's life in the field of long-distance athletic trainer. Using qualitative descriptive research methods with ethnographic methods. The population of this study were coaches, athletes and supporting informants. The sampling technique used was side purposive so that 5 people were obtained with criteria according to research needs. The results of this research show that Wita Witarsa ​​has a good personality and is always willing to learn things that can improve the training process. The key that Wita Witarsa ​​applies is mutual trust between the coach and the athlete, the coach creates and applies it to the athlete with the belief that the athlete is able to complete the program that has been prepared, and the athlete believes in the coach that the program that has been designed is appropriate to the needs and targets set. achieved. Wita Witarsa ​​is inspiring because she has succeeded in producing a number of athletes with various achievements that have made Indonesia proud on the international stage. Based on the research results obtained, it can be said that the coach's personality has a great influence on athletes and their achievements.